Establishing best-practice statements for post-custody community transition: Insights from a modified Delphi study - Majeed, Tazeen; Taylor, Jo; Breuer, Erica; Nepal, Smriti; Remond, Marc; Grant, Luke; Hampton, Stephen; Sullivan, Elizabeth (PloS one, 2025)
The transition from custody to community is a critical juncture for people exiting custody, necessitating substantial support. However, the programs and services providing this support are often fragmented and lack a unified approach in terms of terminology, design, resourcing, timing, delivery, and monitoring and evaluation. This study sought to establish an agreed terminology and promote a broader consensus on best practices relating to these programs and services. We used a two-phased Delphi methodology to provide a structured, formal, and iterative process for gathering and refining the opinions of subject experts, knowledge holders, and people with lived experiences. Using purposive sampling, 160 national and international participants were invited to participate. Comprehensive study protocol has already been published elsewhere. This modified two-phased Delphi study delivers a set of 40 best-practice statements that can be adapted to the individual needs and contexts of different programs and services. These best-practice statements clarify several key themes, including language and terminology, program aims and outcomes, best-practice principles, the significance of an interconnected phased approach, timing related to services and programs, responsibility for funding and coordination of programs, and monitoring and evaluation. This study introduces an umbrella term, 'Transitional and Post-Release Support Programs (TPSP)', to describe programs and services for people exiting custody and provides best-practice statements that can enhance access, documentation, monitoring, and evaluation processes. This study underscores the importance of a value-based approach in TPSPs to foster purposive program design and a human rights-aligned approach to service provision for people exiting custody. The use of umbrella term and the best-practice statements will promote the use of humane, dignified language, a streamlined, timely, structured, and collaborative discourse, and a more cohesive approach to service provision for people exiting custody.